A4.20 Viral expression of TSG-6 can stimulate osteophyte formation in experimental osteoarthritis. (13th February 2015) - Broeren, MGA; Bennin, MB; Arntz, OJ; Blom, AB; van den Berg, WB; van de Loo, FAJ
Abstract : Background and objectives: Tumour necrosis factor-inducible gene 6 (TSG-6, also named TNFAPI6) is upregulated during experimental arthritis in mice (Geurts et al . 2009). The therapeutic efficacy of TSG-6 has been shown in multiple animal models for rheumatoid arthritis, reducing both inflammation and cartilage damage. Recent studies suggest that inflammation can also play a role in early osteoarthritis (OA) pathogenesis (Ayral et al . 2005). Therefore, TSG-6 therapy might also be an effective treatment in inflammatory OA. In this study, we analysed the expression of TSG-6 during experimental arthritis and explored the effects of TSG-6 gene therapy in a murine model of inflammatory osteoarthritis. Materials and methods: TSG-6 gene expression was determined in microarrays of collagenase-induced osteoarthritis at day 7 and day 14 after induction. The murine TSG-6 gene was cloned in a lentiviral and adenoviral vector. Freshly isolated bone marrow-derived dendritic cells (BMDCs) were transduced with the lentiviral vector and subsequently differentiated into osteoclasts on bone slices with M-CSF and RANKL. After 10 days, bone slices were washed and stained using Coomassie Blue and bone resorption was determined using the Leica Application Suite software. To study the effects of TSG-6 in experimental knee osteoarthritis, mice received two intra-articular injections of collagenase. Four days prior to and 20 days after arthritis induction, mice were injected intra-articularly with TSG-6 adenovirus. At day 7, inflammation was assessed using fluorescent Prosense probes. At day 42, knee joints were analysed by X-ray and histological assessment. Results: TSG-6 was upregulated in collagenase-induced OA (2, 6x at day 7 (P < 0.05) and 2.5x at day 14 (P = 0.55)). BMDCs transduced with TSG-6 lentivirus showed strong expression of TSG-6. Bone resorption by BMDC-derived osteoclasts was significantly reduced (20.1% surface erosion with control virus to 10.4%, p = 0.01), providing a possible mechanism for the therapeutic effects in rheumatoid arthritis models. At day 7 of collagenase-induced osteoarthritis, no difference in inflammation was detected using the Prosense probes. At day 42, no improvement on cartilage damage was seen, but X-ray analysis showed strong osteophyte formation at the femur/tibia region in the knee joint. Histological analysis showed that the osteophytes contained both bone and cartilage. Conclusions: Viral expression of TSG-6 can reduce the bone resorption activity by BMDC-derived osteoclasts. The expression of TSG-6 by synovial cells during experimental osteoarthritis results in the formation of osteophytes. These results imply a causative role for TSG-6 in osteophyte formation, supporting the recent finding that TSG-6 activity is associated with radiographic progression of OA (Wisniewski et al . 2014).